Long-term survival of the uncemented Balgrist total hip replacement cup - Gallo, Jiří; Lošťák, Jiří; Langová, Kateřina (International orthopaedics, 2013)
PURPOSE: The purpose of this study was to evaluate the long-term clinical and radiographic outcomes of the Balgrist total hip replacement cup. METHODS: We report the results of a retrospective review of 195 total hip prostheses with Balgrist cup implanted in 178 patients. There were 59 men and 119 women with a mean age at surgery of 52.3 years (range, 19-72). Cox regression was used to determine the influence of independent variables on the survivorship of the prosthesis. RESULTS: There were 117 (66 %) of 178 patients, and 131 (67 %) of 195 hips available for assessment at a mean follow-up of 17.4 years. A total of 21 patients (22 hips) were lost from follow-up (12 %). A total of 25 patients (27 hips) required some type of re-operation during the follow-up period. Eight of 27 re-operations (30 %) were directly caused by the Balgrist cup failure due to fatigue fracture of the metallic shell (n = 5; 19 %), polyethylene wear (n = 2; 7 %) and aseptic loosening (n = 1; 4 %). The mean polyethylene wear rate was 0.068 mm/year (range, 0.008-0.230; SD = 0.043). The risk of re-operation for any reason was decreased with dysplastic hip as a primary diagnosis (hazard ratio; HR = 0.250; 95 % CI 0.086-0.725) and with greater age at the time of surgery (HR = 0.923; 95 % CI 0.880-0.969). The 19-year survivorship with re-operation for any reason was 75.6 % (95 % CI 67.0-84.2). The 19-year survivorship with re-operation for the Balgrist cup failure was 90.5 % (95 % CI 83.4-97.6). CONCLUSIONS: The Balgrist cup continues to provide excellent clinical and radiological outcomes. This is associated at least in part with a low polyethylene wear rate. The main reason for the Balgrist cup failure is fatigue fracture of the metallic shell.
Keywords: dospělí; polyethylen; Longitudinal Studies; ženské pohlaví; Proportional Hazards Models; lidé; Prosthesis Design; kyčelní protézy; senioři; náhrada kyčelního kloubu; incidence; Cohort Studies; Hip Dislocation; Aged; kyčelní kloub; lidé středního věku; Arthroplasty, Replacement, Hip; Humans; luxace kyčle; výsledek terapie; proporcionální rizikové modely; retrospektivní studie; artróza kyčelních kloubů; Hip Prosthesis; kostní cementy; Follow-Up Studies; Polyethylene; mužské pohlaví; reoperace; Adult; Hip Joint; Male; Bone Cements; Reoperation; Kaplan-Meier Estimate; Retrospective Studies; Kaplanův-Meierův odhad; Treatment Outcome; protézy - design; Osteoarthritis, Hip; Middle Aged; kohortové studie; Female; longitudinální studie; následné studie; Incidence